SOCIOECONOMIC DEVELOPMENT IN MUSLIM COUNTRIES: IBN KHALDUN’S DEVELOPMENT MODEL-BASED APPROACH - Ira Eka Pratiwi (Journal of Islamic Monetary Economics and Finance, 2023)
This study constructs a measure of socioeconomic development in Muslim countries based on Ibn Khaldun’s model of development. It proposes a composite index of development based on three dimensions, namely human empowerment, government and institution, and economic growth, and terms it as Ibn Khaldun-based socioeconomic development index (I-SDI). A total of 13 indicators are selected to represent each dimension and are employed for construction of the index using an equal weighted method and additive aggregation approach. In general, we note that many Muslim countries are underperformed., as indicated by the low value of I-SDI. We further find that Muslim countries that perform well in government and institution dimensions tend to experience better socioeconomic development. We believe that the proposed I-SDI is non-redundant and robust and hence can be utilized as an alternative way of measuring the development in Muslim countries. In other words, the Ibn Khaldun’s model of development is exceptionally meaningful in explaining the socio-economic performance of Muslim countries.